Determinasi sumber tekanan dan analisis regangan utama di Gunung Api Papandayan untuk mengetahui korelasi dengan kegempaan - Ony Kurnia Suganda; Dina Anggreni Sarsito; Hasanuddin Zaenal Abidin; Aris Kusnandar (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no2.20072Papandayan volcano is located in the southern part of Garut regency, about 70 km southeast of Bandung, West Java. Monitoring the activities of Papandayan volcano has been done using various methods both continously and periodically, one of them is deformation method using repeated GPS (Global Positioning System) survey. GPS survey method is basically used to obtain the pattern and speed of the deformation body of the volcano, both in horizontal and vertical directions and also could be used to determined the location and size of the strain source of deformation based on Mogi model. By describing the shallow seismic activities before and after the eruption, this could show us the correlation of deformation characteristic and its seismic activities. By the result of eight GPS campaigns show that the deformation acceleration is running rapidly, where the fluctuation of shallow seismic activities are directly followed by inflation and deflation of volcano body. Pressure source movement running up and down to southwest-northeast direction. This correlation will lead us to the more comprehensive phenomena of a volcanic eruption, especially in Papandayan volcano.